(untitled) (Emancipação, 2010)
Este artigo apresenta o resultado de pesquisa desenvolvida como conclusão do Curso de Especialização em Práticas Interdisciplinares Junto à Família, no ano de 2007, visando à sistematização da prática profissional do Assistente Social na Secretaria Municipal de Educação de Telêmaco Borba – PR, no período de junho de 2005 a maio de 2007, junto às famílias das Escolas Municipais e dos Centros Municipais de Educação Infantil – CMEIs, bem como as possibilidades e limites desta prática profissional. Palavras-chave: Prática profissional do Serviço Social. Educação. Família. Abstract: This paper presents the outcome of the research carried out as final paper for the Specialization Course in Interdisciplinary Practices along with the Family in the year 2007, aiming at the systematization of the professional practice of the social assistant in Telêmaco Borba’s Department of Education, from June 2005 to May 2007, along with the families of the Municipal schools and the Municipal Child Education Centers – CMEIs, as well as the possibilities and the limits of these professional practices. Keywords: Professional practices of Social Service. Education. Family.